2020
DOI: 10.3390/molecules25040810
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Green Extraction Methods and Solvents on Bioactive Components of Chamomile (Matricaria chamomilla L.) Flowers

Abstract: Chamomile (Matricaria chamomilla L.) dried flowers contain a group of interesting biologically active compounds such as sesquiterpenes, flavonoids, coumarins, vitamins, phenolic acids and glucosides. Therefore, the aim of the present study was to characterize the composition in bioactive compounds (specialized metabolites) present in water and ethanol extracts of chamomile flowers, together with monitoring the impact of different extraction techniques (conventional vs. ultrasound-assisted extraction (UAE)) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 39 publications
3
20
0
2
Order By: Relevance
“…In a study reported by Das et al (2019), the antioxidant activity of Piper betle leaves was evaluated with different extraction methods such as sonication, soxhlet, maceration, and it was determined that the results obtained with the sonication method were better than other methods (Das et al, 2019). It has been stated that ultrasound‐assisted extraction is new, easy, and cheap compared to other extraction methods (Farahmandfar et al., 2017; Predescu et al., 2016; Zlabur et al, 2020) and is also an alternative technique compared to traditional solvent extraction (Peanparkdee et al., 2018). Additionally, ultrasound‐assisted extraction has been stated as a valuable green alternative procedure to improve solvent extraction of the bioactive compound (Vega Arroy et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study reported by Das et al (2019), the antioxidant activity of Piper betle leaves was evaluated with different extraction methods such as sonication, soxhlet, maceration, and it was determined that the results obtained with the sonication method were better than other methods (Das et al, 2019). It has been stated that ultrasound‐assisted extraction is new, easy, and cheap compared to other extraction methods (Farahmandfar et al., 2017; Predescu et al., 2016; Zlabur et al, 2020) and is also an alternative technique compared to traditional solvent extraction (Peanparkdee et al., 2018). Additionally, ultrasound‐assisted extraction has been stated as a valuable green alternative procedure to improve solvent extraction of the bioactive compound (Vega Arroy et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to being used in traditional medicine, it is also used for tea and vitamin supplements (Al‐Snafi, 2018). Chamomile plant extracts, one of the most consumed herbal teas, have also been reported to many biological activities (Blicharski et al., 2017; Cvetanovic et al., 2015; Molnar et al, 2017; Sotiropoulou et al, 2020; Zlabur et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research, Society and Development, v. 9, n. 12, e29591211070, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i12.11070 As diferenças encontradas acima podem ser justificadas a fatores que vão desde o ambiente de onde a planta foi coletada, como composição do solo, umidade, condições climáticas, estagio de maturação, presença de predadores, até as condições extrativas, tais quais a seletividade e polaridade do solvente, pH, temperatura e método extrativo (Gobbo-Neto & Lopes, 2007;Žlabur et al, 2020). Neste teste obteve-se um valor de CE50 (concentração necessária para causa 50 % do efeito) de 1068 µg.mL -1 superiores aos 1150 ± 7,1 µg.mL -1 obtidos por Skenderidis et al Estimar a extensão da peroxidação lipídica tem grande importância em diversas patologias associadas ao estresse oxidativo, em que espécies reativais de oxigênio atacam várias classes de biomoléculas, incluindo DNA, proteínas e lipídios (Tsikas, 2017).…”
Section: Resultsunclassified
“…The efficient recovery of phytochemicals from natural sources is mainly influenced by the method and the conditions used for extraction [ 27 , 44 , 45 , 46 , 47 , 48 ]. This stage must assure a high extraction performance and preserve the quality of the extracted compounds, in addition to meeting other requirements such as versatility, cost-effectiveness, and ease of operation [ 49 ] The most commonly applied method for the recovery and isolation of natural bioactive substances such as polyphenols is inarguably conventional solvent extraction [ 41 , 42 ].…”
Section: Extraction Procedures Of Polyphenols From Eucalmentioning
confidence: 99%